Behavior of the value of responsibility in fourth-year students of the Dentistry degree - Orisleddys Delgado González; Katia Martínez Delgado; Maritza de la Caridad Barrios González; Yunior González Linares; Liurbys Rodríguez Pino (Edumecentro)
Background: higher education cannot remain distant from the education of values; the value of responsibility acquires a special meaning in Dentistry students when they practice directly with patients. Objective: to describe the behavior of the value of responsibility in fourth-year students of the Dentistry degree at the Dental Clinic Centro, in Ciego de Ávila, during the 2021-2022 academic year. Methods: a descriptive observational study was carried out at the Dental clinic Centro in Ciego de Ávila, at the University of Medical Sciences in that province during the 2021 academic year. Theoretical methods were used: historical-logical, analytical-synthetic and inductive-deductive; and empirical ones: observation through a guide designed with the modes of action of the value of responsibility contextualized to the Dentistry degree, grouped into three dimensions. The percentage was used as a statistical method. Results: It was found that 46.15% of students behaved responsibly, 38.46% behaved irresponsibly, and 15.38% behaved irresponsibly in their corresponding tasks. The most affected dimensions were responsibility in studying and in the work environment. The most affected indicators were: adequately developing the clinical history and maintaining an ethical and professional attitude in the work environment. Conclusions: The behavior of the value of responsibility of fourth-year Dentistry students was described; the results indicate deficiencies that are feasible to modify in a positive sense through educational interventions.